ANALYSIS STRUCTURE THE PT. TEMPO LAND BUILDING - Manthofani, Subhan; Firmanto, Arief (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2017)
Mundu? is? an? area? in? the? district of? Cirebon? that? passed? by? the Pantura lane, in the area of the Mundu there are various kinds of? trading industry, one of which is the trading industry from PT.? TEMPO LAND that are producing? medicines? for? health.? In? order? to? create? a? good? production and? marketing, so? in? the? area? is? built? office production? and? marketing? of PT. TEMPO LAND.PT.? TEMPO? LAND? is? a? group? company? in? the? form? of? by? the TEMPO GROUP or PT. TEMPO SCAN PACIFIC Tbk . The company PT. TEMPO GROUP? started? its? business? on? November 3, 1953. Production from this company produces a variety of pharmaceutical and healthcare products with different brands.?? In? order? to? create? a? structure? that? is? safe? and? meets serviceability limit, so in the process of design the building structure must be according? to? SNI? - 2847? - 2013? of? reinforced? concrete,? which? is? the latest regulations adapted from the latest material technology development refers to the AISC. Beside planning, the? loading? structure? must? be according to SNI ? 1727 ? 2013 , then? for? calculation? of? earthquake engineering refers to SNI ? 1726 ? 2012.Analysis? structure? using? SAP2000,? for? the? material? of? structures? is used? concrete? including? frame? section? (column,? sloof,? beam,? and? slab). And then the? result? from? analysis? are? the? PT.? TEMPO? LAND? building? is safe? or? not,? with? check? the? deflection? and? check? load? maximum? permit from analysis foundation of PT. TEMPO LAND.Keywords : Analysis structure, SAP2000, frame section, deflection.